Impacts of using a piezo-mounted elastic fin energy harvester on the power production and heat transfer control in a ventilated cavity during turbulent forced convection - Selimefendigil, Fatih; Altammar, Hussain; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2024)
Piezo-electric energy harvesters (PE-EH) are used in a variety of engineering applications due to their simplicity, ease of installation, compact structure, higher power density, and lower cost. In this study, a novel elastic PE-EH fin assembly within a ventilated cavity is proposed for thermal management and power production during forced convection in turbulent flow regimes by using finite element method with ALE. Impacts of Reynolds number (Re between 10,000 and 50,000), opening ratio (OR between 0.5 and 2), fin vertical placement (yf between -0.3H and 0.3H), and inlet port horizontal position (xi between 0 and 0.6H) on the characteristics of generated power and convective heat transfer are numerically assessed. Higher deflection of the elastic fin assembly and vortex size reduction at the fin tip are the outcomes of higher Re and OR values. The average Nu rises by about 135% for Re values between Re = 10,000 and Re = 30,000 but reduces by 55% between Re = 30,000 and Re = 50,000. Cooling performance is improved by 165% when OR variation is taken into account, going from the lowest value of OR to OR = 1.5. For generated power, the enhancement factors are 290 and 81 when values of Re and OR are raised from their lowest to highest levels. For cooling performance and generated power, the corresponding improvement factors are 6.94 and 2.5, respectively, from the lowest to the maximum value of the vertical position. Inlet and outlet port locations closer to the middle of the top and bottom wall provides the highest power generation from the PE-EH. There are 121% and 41% variations of generated power when inlet and outlet port locations are varied. An artificial neural network is used to assess the power generated by the PE-EH device using a three-input, one-output system.
Keywords: Piezo-electric; Energy conversion; Finite element method; Vented cavity; Artificial neural network